2008
DOI: 10.1007/s10569-008-9146-5
|View full text |Cite
|
Sign up to set email alerts
|

The relativistic factor in the orbital dynamics of point masses

Abstract: There is a growing population of relativistically relevant minor bodies in the Solar System and a growing population of massive extrasolar planets with orbits very close to the central star where relativistic effects should have some signature. Our purpose is to review how general relativity affects the orbital dynamics of the planetary systems and to define a suitable relativistic correction for Solar System orbital studies when only point masses are considered. Using relativistic formulae for the N body prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…As mentioned in Refs. [1][2][3][4], the influence exerted by general relativity upon the dynamics of the bodies in our Solar System should not be neglected. In particular, Wanex [2] demonstrated that the difference between the final positions of Newtonian and relativistic trajectories in the restricted three-body problem made of a space probe, the Earth, and the Moon becomes considerably larger for bounded chaotic orbits than for bounded regular orbits.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Refs. [1][2][3][4], the influence exerted by general relativity upon the dynamics of the bodies in our Solar System should not be neglected. In particular, Wanex [2] demonstrated that the difference between the final positions of Newtonian and relativistic trajectories in the restricted three-body problem made of a space probe, the Earth, and the Moon becomes considerably larger for bounded chaotic orbits than for bounded regular orbits.…”
Section: Introductionmentioning
confidence: 99%
“…Galactic star clusters with massive central black holes [1,2], triple systems with a relativistic compact inner binary [3,4,5,6,7,8], binary black hole coalescence in the presence of a third body [9,10,11], and even the stability of the solar system [12] have been studied using combinations of N-body techniques and relativistic dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Naoz et al (2013) provide the full Hamiltonian for a triple system (see also Schäfer 1987). The equations of motion are given by Newhall et al (1983) and Benitez & Gallardo (2008). These accelerations and Hamiltonian are implemented in gr full.…”
Section: Appendix A: Operator Theorymentioning
confidence: 99%